2016
DOI: 10.1093/arclin/acw051
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Healthcare Decision-making Capacity

Abstract: It is often necessary for neuropsychologists, clinical psychologists, and other healthcare professionals to assess an individual's capacity to consent to treatment related to healthcare. This task can be challenging and requires a delicate balance of both respect for individuals' autonomy, as well as the protection of individuals with diminished capacity to make an autonomous decision. The purpose of the present review is to provide an overview of the conceptual model of decisional capacity as well as a brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 82 publications
0
69
1
8
Order By: Relevance
“…While the absence of an association of neuropsychiatric symptoms with decisional capacity was contrary to our hypotheses, it parallels findings in schizophrenia where psychotic symptoms appear to be less predictive of capacity to consent to research or treatment than cognitive deficits (Palmer & Savla, 2007; Palmer et al, 2012). Note that mean levels of neuropsychiatric symptoms in our AD sample were low relative to the potential range of the CGA-NPI.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…While the absence of an association of neuropsychiatric symptoms with decisional capacity was contrary to our hypotheses, it parallels findings in schizophrenia where psychotic symptoms appear to be less predictive of capacity to consent to research or treatment than cognitive deficits (Palmer & Savla, 2007; Palmer et al, 2012). Note that mean levels of neuropsychiatric symptoms in our AD sample were low relative to the potential range of the CGA-NPI.…”
Section: Discussioncontrasting
confidence: 86%
“…Severity of cognitive deficits is a significant predictor of impaired decisional capacity (Palmer & Savla, 2007; Palmer, Savla, & Harmell, 2012). However, in addition to the cognitive deficits that typify AD, this disorder is frequently associated with neuropsychiatric symptoms such as mood disturbances, delusions, hallucinations, and agitation (Burke, Hall, & Tariot, 2013; Cantillon, De La Puente, & Palmer, 1998; Cummings & Zhong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, empirical research has consistently shown that severity of cognitive deficits, rather than severity of primary psychopathologic symptoms, to be the strongest predictor of decisional capacity (reviewed in Palmer & Harmell, 2016). However, decision making capacity is an inherently context-dependent construct – affected by the inherent complexity of the information and decision, as well as the manner in which the information is communicated complexity (Dunn, Palmer, & Karlawish, 2007).…”
Section: Decision Making Capacity In People With Smimentioning
confidence: 96%
“…placebo treatments). Furthermore, Palmer and Harmell (2016) reported association between certain neurocognitive domains and healthcare decision-making, such as episodic memory, naming, working memory, executive functions and speed. The authors also summarised previously findings of what cognitive abilities appear to be correlated to different components of decision-making capacity:…”
Section: Associated Cognitive and Linguistic Functionsmentioning
confidence: 99%
“…Estimation of cognitive severity by for example Mini Mental State Examination (MMSE; Folstein, Folstein & McHugh, 1975) Karlawish, 2017;Palmer and Harmell, 2016;Lamont, Jeon & Chiarella, 2013;Pennington et al, 2018). Some well-established instruments to assess different aspects of the capacity are:…”
Section: Testsmentioning
confidence: 99%